Wear patterns of compartments in varus knee osteoarthritis among an Asian population: a cross-sectional study with radiographic and intraoperative analysis - Loh, Kwong Weng; Ayob, Khairul Anwar; Che-Hamzah, Fahrudin; Merican, Azhar Mahmood; Sulaiman, Shahrul Hisham; Lee, Joo Ann; Tiew, Sei Kern (Springer Nature, 2025)
Purpose: Osteoarthritis (OA) of the knee significantly impairs mobility and quality of life. Knee arthroplasties have dramatically improved patient outcomes, allowing individuals to regain independence. Unicompartmental knee arthroplasty (UKA) is a surgical option for patients with isolated single-compartment disease, offering the benefits of reduced surgical time and minimized surgical risks. However, the appropriateness of UKA is often underestimated. Therefore, this study aims to determine the proportion of patients with varus knee OA who are suitable candidates for UKA. Methods: A prospective cross-sectional study was conducted on 207 knees undergoing knee arthroplasty surgery for varus knee OA. Pre-operative radiographs were graded using both the Kellgren-Lawrence (KL) and modified Keyes classifications. Intra-operatively, the knees were inspected, and photographs of the tibial cut were reviewed by a neutral observer. The appropriateness of UKA was determined based on these evaluations. Results: The lateral compartment was not involved in 169 (81.6%) knees. Only six (2.9%) knees had a KL grade 4 involvement of the lateral compartment. After excluding patients with isolated medial compartment OA, no radiographic evidence of lateral and patellofemoral involvement, and a grade 1 on the modified Keyes classification, we found that 79 (38.2%) patients were suitable candidates for a medial UKA. Intraoperatively, 84 (40.6%) patients had a functional ACL with no observable wear in the lateral and patellofemoral joint (PFJ) compartments. Conclusion: In patients with varus knee OA, a significant proportion have wear patterns suitable for management with a UKA. Identifying these patients requires targeted examinations and specific radiographic views.